2014
DOI: 10.4067/s0718-18762014000200006
|View full text |Cite
|
Sign up to set email alerts
|

A Metrics-Driven Approach for Quality Assessment of Linked Open Data

Abstract: This paper is available online at www.jtaer.com DOI: 10.4067/S0718-1876201400020000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 15 publications
0
45
0
8
Order By: Relevance
“…In their research, Behkamal et al (2014) found that public sector open data is sometimes mapped with incorrect values, questioning the credibility and quality of the data being made publicly available. At the same time, such data fails to cater to the information needs that an individual might be interested in, putting in question the compatibility of the data being opened to public.…”
Section: Compatibilitymentioning
confidence: 99%
“…In their research, Behkamal et al (2014) found that public sector open data is sometimes mapped with incorrect values, questioning the credibility and quality of the data being made publicly available. At the same time, such data fails to cater to the information needs that an individual might be interested in, putting in question the compatibility of the data being opened to public.…”
Section: Compatibilitymentioning
confidence: 99%
“…The ISO 25012 data quality model (ISO 2008) defines 15 data quality attributes and classifies them into inherent quality and system-dependent quality. Some of the existing research on data quality uses the quality model as a basis, such as (Behkamal et al 2014;Rafique et al 2012). Data quality evaluation is challenging because data quality cannot be judged without considering the context or situation at hand (Nurse et al 2011;Bizer 2007;Bizer and Cyganiak 2009).…”
Section: Quality Of Open Datamentioning
confidence: 99%
“…[3,2]). Our study considers some of those dimensions, and particularly the ones introduced in [19], namely:…”
Section: Open Data Quality Dimensionsmentioning
confidence: 99%